The use of Messenger for research collaboration: An auto-ethnographic study - Alonzo, Dennis; Oo, Cherry Zin (Frontiers in Psychology, 2023)
The use of social media for the collaboration of academics has been increasing in recent years. However, there are no reported studies on using Messenger as a collaborative platform to write and publish journal articles and apply for research and development grants. We use an auto-ethnography to reflect on our experiences over the last three years, using Messenger as our medium for our ongoing collaborative research activities. Our results highlight the benefits and challenges of using social media for this engagement. The capabilities of Messenger, as opposed to traditional correspondence through email, have paved our preference to use this platform. We can engage in dynamic collaboration and focused discussion with less formal communication conventions through Messenger. In addition, the extra features, including easy phone calls, sending links, resources and screenshots, and using emojis and stickers for more socially cohesive interactions, are valued features of Messenger. We used the activity theory to highlight the interrelationships of factors (i.e., personal, social-emotional, structural, technological, and organisational) contributing to the success of collaborative academic activities, including the successful publication of journal articles and securing research and development grants. The findings of our study significantly contribute to understanding how social media can be effectively used for academic engagement.